Back Cover Maharot Vol. 6, No. 1, Januari – Juni (2022) - Back Cover Maharot Vol. 6, No. 1, Januari – Juni (2022) (Maharot : Journal of Islamic Education, 2022)
Back Cover Maharot Vol. 6, No. 1, Januari – Juni (2022)